miR-34 modulates apoptotic gene expression in Ingenol mebutate treated keloid fibroblasts - De Felice, Bruna (Mol Med Rep, 2018)
Keloids are benign skin tumors that develop in individuals who have a positive family history of keloid disorders. Keloids are characterized by a deregulated wound-healing process, atypical fibroblasts with extreme deposition of extracellular matrix components, particularly collagen, increased cell proliferation and associated failure of apoptosis. Recently ingenol-mebutate has been used as a novel agent with anti-proliferative activity on human keloids as an alternative treatment option in patients, once conventional therapies have failed. We hypothesized that microRNAs (miR/miRNA) may be involved in the balance between lesion formation and repair. A comprehensive understanding of the molecular mechanism underlying the Ingenol-mebutate response in keloid fibroblast following Ingenol-mebutate exposure has been established previously. Therefore, the present study analyzed changes in miRNAs and apoptotic gene regulation in Ingenol-mebutate treated keloid fibroblast, by reverse transcription-quantitative polymerase chain reaction and a DNA fragmentation assay. The range of upregulated miRNAs and downregulated genes encoding cell death appeared to be associated with the degree of the morphological alterations in Ingenol-mebutate treated keloids. In particular, the upregulation of miR-34a was detected in keloid fibroblasts during and following Ingenol-mebutate exposure. Keloid fibroblasts that overexpressed miR-34a showed differential expression of genes involved in the apoptotic signaling pathway such as p53. In conclusion, the Ingenol-mebutate treatment used here was effective in reducing keloid fibroblast growth in cell culture experiments and the expression of particular miRNAs modulated the pro-apoptotic gene expression following Ingenol-mebutate treatment.